Kefektifan Konseling Kelompok Solution-Focused Brief Counseling untuk Meningkatkan Self-Control pada Siswa SMP Negeri 80 Jakarta - Taklal, Selvi Afliana; Delviana, Evi; Nugroho, Andreas Rian; Gunawan, Ronny (Universitas Mathla'ul Anwar Banten, 2025)
Self-control is the ability to regulate, plan, and direct behavior to achieve positive goals. Low self-control can hinder personal development and success in life. Junior high school students, who are in a phase of rapid physical, cognitive, and emotional changes, are particularly vulnerable to deviant behaviors when lacking self-control. Enhancing self-control at this stage is therefore crucial. This study aims to assess the effectiveness of group counseling using the Solution-focused brief counseling (SFBC) approach in improving self-control among students at SMP Negeri 80 Jakarta. This quantitative study used a one-group pre-test and post-test design. The population consisted of 66 students, with a sample of three students identified through low self-control scores on a questionnaire. One of sample is a student with special needs. The intervention involved five group counseling sessions using the SFBC approach. Data were collected through observation and questionnaires and analyzed using a one-sample t-test with SPSS version 26. Results showed significance values of 0.002 (pre-test) and 0.011 (post-test), indicating the SFBC approach effectively improved students’ self-control.